2017
DOI: 10.1093/aje/kww198
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Blood Pressure Trajectories of Preterm Children: The Role of Family and Neighborhood Socioeconomic Status

Abstract: Racial disparities in cardiovascular disease mortality in the United States remain substantial. However, the childhood roots of these disparities are not well understood. In the current study, we examined racial differences in blood pressure trajectories across early childhood in a sample of African-American and European-American low-birth-weight preterm infants. Family and neighborhood socioeconomic status (SES), measured at baseline, were also examined as explanations for subsequent group disparities. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Multiple regression analyses adjusting for site were used to identify antenatal, neonatal, social, and demographic factors that predicted BP ≥90th percentile and BP ≥95th percentile on the basis of systolic BP, diastolic BP, and/or systolic or diastolic BP for the total cohort and for the subgroup of children of normal or low weight at 6 to 7 years. Independent variables associated with hypertension including male sex, 4 public insurance as a marker of poverty, 2629 being multiracial, 30 maternal hypertension in pregnancy, 2,7 GDM, 31 and weight gain velocity 2,11 were selected on the basis of the literature. The same model was run for the subgroup of children who were normal weight or low weight at the visit.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple regression analyses adjusting for site were used to identify antenatal, neonatal, social, and demographic factors that predicted BP ≥90th percentile and BP ≥95th percentile on the basis of systolic BP, diastolic BP, and/or systolic or diastolic BP for the total cohort and for the subgroup of children of normal or low weight at 6 to 7 years. Independent variables associated with hypertension including male sex, 4 public insurance as a marker of poverty, 2629 being multiracial, 30 maternal hypertension in pregnancy, 2,7 GDM, 31 and weight gain velocity 2,11 were selected on the basis of the literature. The same model was run for the subgroup of children who were normal weight or low weight at the visit.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies have indicated that, on the whole, AAs live in far less advantaged neighborhoods than EAs (Fuller-Rowell, Curtis, Klebanov, Brooks-Gunn, & Evans, In Press; Osypuk, Galea, McArdle, & Acevedo-Garcia, 2009; Rossen, 2013; Roux et al, 2001). The historical factors underlying race differences in neighborhood quality (eg, discriminatory policies) are well understood (Coates, 2014), as are the related processes of stigma and racism that have played a role in creating and sustaining neighborhood segregation (Massey, 2007).…”
mentioning
confidence: 99%
“…One recent study found that AA families making upwards of $100,000 typically live in the kinds of neighborhoods inhabited by EA families making $30,000 or less (Sharkey, 2014). Furthermore, although neighborhood factors generally account for a portion of the association between family socioeconomic status and health outcomes, each of these variables have been found to exert independent effects on health and often account for unique variance in racial health disparities (Chen & Paterson, 2006; Fuller-Rowell, Curtis, Klebanov, et al, In Press; Robert, 1998; Roux et al, 2001). …”
mentioning
confidence: 99%
“…Exclusion of BIPOC researchers and participants and lack of depth in considering race and racism in environmental health and epidemiology have harmful consequences on environmental health protections for all. Analyses supporting biological bases for racial health disparities still emerge in top journals [ 109 ] even where an environmental basis might be more probable [ 139 , 140 ]. Theories that poor health results from genetic differences have eugenic undertones and ramifications beyond only population health.…”
Section: Discussionmentioning
confidence: 99%